'Britten Minor': Constructing the Modernist Canon. Issue 2 (25th July 2016) - CHOWRIMOOTOO, CHRISTOPHER
Abstract: In the last few decades, established narratives of twentieth-century music – with Schoenberg and his disciples at the centre and others on the periphery – have come under considerable fire: some have denounced the modernist canon itself as narrow and esoteric, while others have sought to restore marginalized 'minor' composers to a supposedly rightful centrality. In this article, I revisit the mid-century process of canon formation in order to excavate a deeper, less divisive understanding of its history. Using Benjamin Britten as a case study, I sketch a more ambivalent and reciprocal relationship between major and minor composers than has often been suggested. After illuminating key tropes in Britten's mid-century reception, I examine how the composer and his critics fashioned his canonical minority and, in the process, helped to construct the 'majority' of his modernist counterparts. I argue that, far from marginalizing his oeuvre, Britten's ambivalent, peripheral, and even diminutive relationship with the 'major' figures of musical modernism was central both to his mid-century appeal and his enduring place in the canon. Ultimately, I suggest that attending to Britten's complex and self-conscious canonical negotiations can teach us a lot not just about his own role in history, but also about the wider ways that twentieth-century canons are negotiated, mediated, transmitted, and performed.